2013
DOI: 10.3109/02713683.2013.847960
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Tear Meniscus with Optical Coherence Tomography in Thyroid-Associated Ophtalmopathy

Abstract: Tear function is significantly disturbed in GD. OCT is an effective way to assess the tearing function also in patients with GD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Some metric variables of the menisci appeared to be reduced in the elderly and in patients with dry eye or thyroid-associated ophthalmopathy. Conversely, higher tear volume was found in MGD patients with corneal damage [47,[54][55][56].…”
Section: Tear Meniscusmentioning
confidence: 87%
See 1 more Smart Citation
“…Some metric variables of the menisci appeared to be reduced in the elderly and in patients with dry eye or thyroid-associated ophthalmopathy. Conversely, higher tear volume was found in MGD patients with corneal damage [47,[54][55][56].…”
Section: Tear Meniscusmentioning
confidence: 87%
“…Some metric variables of the menisci appeared to be reduced in the elderly and in patients with dry eye or thyroid-associated ophthalmopathy. Conversely, higher tear volume was found in MGD patients with corneal damage [47,[54][55][56]. However, although OCT imaging is capable of measuring quantitatively the tear meniscus in terms of height, depth, radius of curvature and area, none of these variables are predictive of the TF thickness [45].…”
Section: Tear Meniscusmentioning
confidence: 99%
“…Points on the grading scale that did not occur in any group are not shown. Palakuru et al 2007Palakuru et al , 2008Ibrahim et al 2010;Koh et al 2010;Chen et al 2011;Park et al 2012;Qiu et al 2012;Altan-Yaycioglu et al 2013;Fukuda et al 2013;Bartuzel et al 2014;Canan et al 2014;Sizmaz et al 2014;Akiyama et al 2015;Tukenmez-Dikmen et al 2015). For measuring precorneal tear film, the resolution of commercially available OCT systems is not sufficient for quantitative measurement.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, tear meniscus can be quantified by AS‐OCT in terms of tear meniscus height, tear meniscus depth, and tear meniscus area, measured directly after blinking . This enables a myriad of experimental data to be generated; for instance Sizmaz et al have shown that patients with Graves’ disease have lower tear meniscus height …”
Section: Resultsmentioning
confidence: 99%